Acute limb ischemia caused by incorrect deployment of a clip-based arterial closure device - Łukasz Dzieciuchowicz; Maciej Zmysłowski; Karolina Stefaniak; Grzegorz Oszkinis (Videosurgery and Other Miniinvasive Techniques, 2016)
Failure of a vascular closure device most commonly results in a hemorrhage or pseudoaneurysm formation. In this paper a rare case of severe acute limb ischemia following incorrect deployment of a clip-based closure device (Starclose SE, Abbott Vascular) in a 31-year-old woman is presented. Symptoms of acute limb ischemia occurred at the start of the ambulation, 6 h after completion of the procedure. Because of the severity of ischemia the patient was treated surgically, and limb perfusion was successfully restored. An attempt of closure of an inadvertently punctured narrow superficial femoral artery was identified as the cause of this complication.